HUBUNGAN ANTARA TINGKAT PARTISIPASI SISWA DALAM MENGIKUTI OLAHRAGA EKSTRAKURIKULER BOLA BASKET DAN KEDISIPLINAN SISWA DI SMK N 1 CIMAHI - Dikusumah, Reja Sandy Permana (2012)
Reja Sandy Permana Dikusumah. NIM 050166. Physical Education Health and Recreation Studies Program. The Relationship Between Student Participation In Extracurricular Sports Basketball Following And Discipline Students in SMKN 1 Cimahi. Supervisor I: Drs. H. Yus Solihin Y, M.Ed, Supervisor II: Dr. Bambang Abduljabar, M.Pd The forms of student activities at the school today is less supportive and encouraging the formation of a good mental discipline, this happens because the student activity is influenced by environmental factors likely contrary to the rules and norms of the school. The purpose of this study was to determine the relationship between the level of student participation and student discipline. Sampling technique is saturated sampling as many as 20 students. The results showed that the relationship participation of students with low learning discipline. two variables correlation value is 0,32. This correlation indicates that the participation of students still can be variables which contribute to student discipline. CONCLUSIONS: There was no significant relationship between participation in the learning disciplines.